FANCF hypomethylation is associated with colorectal cancer in Han Chinese - Yu, Hang; Pan, Ranran; Gao, Tong; Wu, Dongping; Ying, Jieer; Duan, Shiwei (Turkish Journal of Gastroenterology, 2020)
Background/Aims: FANCF is known to be involved in DNA repair, and overexpression of FANCF protein leads to cell proliferation and ultimately to cancer. The purpose of this study was to assess whether FANCF methylation was associated with CRC.Materials and Methods: A case-control experiment was conducted to study the association between FANCF methylation and CRC. We used qMSP to measure the FANCF promoter methylation, and the percentage of methylation reference (PMR) to quantify the FANCF promoter methylation level. To investigate the effect of the selected FANCF fragment on gene expression regulation, we also performed a dual luciferase reporter gene assay.Results: The results indicated that FANCF methylation in CRC tumor tissues was significantly lower than in non-tumor tissues (median PMR: 44.86% vs. 65.77%, p=1E-5). Analysis of receiver operating characteristic curves showed that FANCF hypomethylation had a diagnostic value for CRC (AUC = 0.670, sensitivity = 55.8%, specificity = 71.7%, p=1E-5). Dual luciferase reporter assay showed that the FANCF fragment up-regulated gene expression (fold change = 1.93, p=0.002).Conclusion: Research demonstrates for the first time that FANCF hypomethylation is significantly associated with CRC risk. FANCF hypomethylation may ultimately increase the risk of CRC by up-regulating the expression of FANCF.